Enforcement and immigrant location choice - Tara Watson (Federal Reserve Bank of Boston, 2013)
This paper investigates the effect of local immigration enforcement regimes on the migration decisions of the foreign-born. Specifically, the analysis uses individual-level American Community Survey data to examine the effect of recent 287(g) agreements, which allow state and local law enforcement agencies to enforce Federal immigration law. The results suggest that one type of 287(g) agreement - the controversial local task force model emphasizing street enforcement - nearly doubles the propensity for the foreign-born to relocate within the United States. The largest effects are observed among non-citizens with at least some college education, suggesting that 287(g) policies may be missing their intended targets. No similar effect is found for the native-born. After the extreme case of Maricopa County is excluded, there is no evidence that local enforcement causes the foreign-born to exit the United States or deters their entry from abroad or from elsewhere in the United States. Rather, 287(g) task force agreements encourage the foreign-born to move to a new Census division or region within the United States.
Keywords: K00; 330